Optimalisasi Pendapatan Asli Daerah (PAD) Berbasis Entrepreneurial Government Untuk Sektor Kesehatan di Kabupaten Karawang Tahun 2023 - Cinta Maulana Putri, Bella; Kartini, Dede Sri; Akbar, Idil (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
This study examines the efforts of the Karawang Regency government to optimize Regional Original Revenue (PAD) through entrepreneurial government in the health sector. Based on the 1945 Constitution, taxes and other levies are allocated to improve local communities. Law Number 2 of 2022 encourages local governments to enhance economic growth and self-sufficiency. In 2023, Karawang Regency exceeded its PAD targets, reflecting effective management. This research evaluates strategies for PAD optimization and the application of entrepreneurial government principles, which include innovation, partnerships, public entrepreneurship, and proactive policies. The findings indicate that these efforts not only increased PAD but also improved public service delivery, promoting sustainable economic growth. The conclusion is that the Karawang Regency Government has successfully formulated strategies to enhance community welfare through PAD optimization in the health sector.